Assessment and Evaluation of Early Childhood Education Institutions - Koenarso, Dyah Ageng Pramesty (THUFULA, 2023)
Assessment is a systemic and continuous process or activity to collect information about the process and learning outcomes of students in order to make decisions based on certain criteria and considerations. This study aims to determine the reality of assessment and evaluation conditions in early childhood education. This study used a qualitative approach and was conducted in five A-accredited ECE institutions in Banjarbaru City. The techniques used to collect data were by interview, observation and documentation. Data analysis used in this study followed the Miles and Hubermen model. Based on the results of the research, the five institutions use 3 types of assessments in their implementation for their students, namely diagnostic assessments, formative assessments, and summative assessments. The results of children's reports to parents in the form of report cards each semester which use checklist techniques, work results, anecdotal records, and serial photos. The activity of reporting the results of children's assessments to parents is carried out every semester. So if the school has already completed the semester, the results of the assessment will be given to the children's parents. The report form for each semester is in the form of a report card. So the report card will represent all children's assessments in their learning.